ROLE OF SHARE OWNERSHIP AND DIVIDEND POLICY ON FINANCIAL PERFORMANCE (CASE STUDY AT CONSTRUCTION SERVICE COMPANY) - Yeni Sofiana; Ananda Dwi Lestari; Agus Sukoco; M. Ikhsan Setiawan; Dani Hermanto (AIBPM Publisher, 2018)
The purpose of this study is toanalyze financial performance seen on the basis of share ownership and dividend policy of the construction services companylisted in Indonesia Stock Exchange (IDX) during 2014-2016. This study analyzes the role share ownership and dividend policy of the construction services company and their impact on finance performance. Method, Data of this research is Construction Company listed on the Indonesia Stock Exchange which reports Consolidated Financial Statements and audited in 2014-2016. The analytical technique used is Multiple Regression Analysis. The data is financial statements downloaded from Indonesia Stock Exchange website and tested with SPSS 24 application. Result, Result of this study is that the performance of Construction Company is influenced by Managerial Ownership positively and significantly affects all financial performance indicators, both Net Profit Margin, Return On Asset and Return On Equity, Institutional ownership has a negative and insignificant effect on financial performance indicator of Net Profit Margin and Return On Equity. While on Return On Asset have positive effect but not significant. Dividend policy negatively affects all financial performance indicators. However significant to Net Profit Margin and Return On Equity, while on Return On Asset is not significant. The findings of this study are contruction company that go public in Indonesia, their finance performance is determined by the value of Managerial Ownership Financial Statement and ROE and this will assist to provide useful information to other researchers, investors and banking companies Keywords: Managerial Ownership, Institutional Ownership, Dividend Policy, Financial Performance